Optimization of parameters of a copper plasma jet produced at the plasma focus device. (24th August 2017) - Kasperczuk, A.; Paduch, M.; Tomaszewski, K.; Miklaszewski, R.; Jach, K.; Swierczynski, R.; Stepniewski, W.; Zielinska, E.; Szymaszek, A.
Abstract: The paper is aimed at optimization of parameters of a copper plasma jet produced at the DPF-1000U device, in which the inner electrode face was conically shaped. Preliminary information was obtained by numerical simulations of the plasma jet creation for different copper cones with the use of the two-dimensional magneto-hydrodynamic code KAROL. The simulations suggested that the cone height in the range of 4–7 cm should ensure a good plasma jet quality. The experimental data delivered by means of a 16-frame laser interferometer and a four-frame X-ray pinhole camera fully confirmed this conclusion. In the paper, we demonstrate the results for a 5 cm height cone. The eroded Cu plasma, swept up by the deuterium plasma sheath, was accelerated axially and compressed to very small diameter (3 mm) with an electron density of 7 × 10 18 cm −3 . The Cu plasma jet achieved a velocity of 5 × 10 7 cm/s and reached in the period of about 230 ns a distance (length) of 7 cm. The above results prove a successful adaptation of the plasma focus device to the metallic plasma jet generator.